Core-shell nano-enzyme as well as preparation method and application thereof
By using spherical CeO2 nanoparticles with ZIF-8 shell and tannin-coated core-shell nanoenzymes, the problems of limited activity and insufficient targeting of existing nanoenzymes on diabetic wounds are solved, and high efficiency on wounds is achieved ROS clearance and inflammation suppression promote rapid healing of wounds.
Patent Information
- Application Number
- CN202411501448.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-25
AI Technical Summary
The existing nanoenzymes have limited activity in diabetic chronic wounds, and it is difficult to improve the targeting of antibacterial materials, while reducing damage to normal cells in the human body.
Spherical CeO2 nanoparticles are used as the core, and zeolite imidazole ester skeleton material ZIF-8 is used as the shell, and tannin is coated on the shell to form a core-shell nanoenzyme. The nanoenzyme gradually decomposes in an acidic microenvironment, releases the CeO2 core, exerts catalytic activity, and eliminates excessive ROS generated by the wound.
It improves the antibacterial, antioxidant and anti-inflammatory properties of nanoenzymes, enhances its targeting ability to diabetic wounds, reduces damage to normal human cells, and achieves rapid healing of wounds.
Smart Images

Figure CN119424474A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of pharmaceutical preparations, and in particular to a core-shell nanozyme and a preparation method and application thereof. Background Art
[0002] Nanozymes are a class of nanomaterials with enzyme-like catalytic activity. Since they were reported in 2007, nanozyme research has entered a period of rapid development. The antibacterial effect of nanozymes is based on their peroxidase activity: nanozymes catalyze hydrogen peroxide (H2O2) to produce highly active hydroxyl radicals (·OH), which in turn destroy the bacterial structure and achieve an antibacterial effect. However, studies have shown that nanozymes have limited activity in diabetic chronic wounds. In addition, while maintaining the efficient catalytic activity of nanozymes, how to improve the targeting of antibacterial materials and reduce the damage of nanozymes to normal human cells is also an important scientific problem that must be solved in nanozyme therapy research, which is of great significance to the rapid healing of wounds.
[0003] In the field of nanozymes, cerium-based nanozymes have attracted extensive attention at home and abroad due to their unique physical and chemical properties. 3+ and Ce 4+ The mixed valence states and oxygen vacancies of CeO2 can be switched between different valence states to obtain better catalytic activity. It has oxidizing and antioxidant properties to different reaction substrates under different reaction conditions. This property makes CeO2 have catalytic properties and a variety of artificial simulated enzyme activities, including oxidase, catalase, peroxidase, superoxide dismutase, and even phosphatase activities. It has also been reported that cerium oxide nanoparticles with a diameter of less than 5nm exhibit high ROS scavenging activity. However, common CeO2 nanozyme preparations all combine precious metals with CeO2 nanoparticles, such as the Chinese patent document CN118304433A, which discloses a Pt / CeO2 nanozyme particle; it includes single-atom Pt and CeO2 nanoparticles combined therewith; the Pt / CeO2 nanoparticles are modified by PEG, and the nanozyme has unique catalytic properties, especially in terms of ROS scavenging and inflammation inhibition. Summary of the invention
[0004] In order to overcome at least one of the problems existing in the above-mentioned prior art, the present invention provides a CeO2 core-shell nanozyme and a preparation method and application thereof. The nanozyme is particularly suitable for ROS removal and inflammation inhibition in diabetic wounds.
[0005] One aspect of the present invention provides a core-shell nanozyme, which is composed of a spherical CeO2 nanoparticle core, a zeolite imidazolate framework material ZIF-8 shell, and tannic acid TA coated on the shell.
[0006] Zeolitic imidazolate framework material, namely ZIF-8, as a metal organic framework (MOF), is non-toxic and has good biocompatibility. At the same time, tannic acid (TA) on the shell of ZIF-8 material can further endow nanozymes with additional biological activities, such as antibacterial, anti-inflammatory and antioxidant properties. 3+ and Ce 4+ The spherical CeO2 nanoparticles have abundant surface oxygen vacancies, which can be converted into oxygen by CeO2. 4+ / Ce 3+ The reversible transformation between CeO2 and CeO2 is used to regulate the activity of CeO2 nanoparticles, which gives them strong antioxidant capacity. At the same time, due to their regular morphology and nanometer size, spherical CeO2 nanoparticles have extremely high specific surface area, which makes them show more efficient reaction activity. Spherical CeO2 nanoparticles are tightly bonded to the shell material, and finally the obtained core-shell nanozymes are also spherical. Spherical CeO2 is encapsulated in ZIF-8 as a core component, temporarily limiting its SOD and various enzyme activities, but as the ZIF-8 structure gradually decomposes in the acidic microenvironment, the CeO2 core is gradually released, exerting its SOD and nanozyme activities, eliminating the excessive ROS produced by the wound, and having a sustained release effect. Coating with tannic acid can improve the biocompatibility of nanozymes and also improve the dispersibility of nanoparticles.
[0007] Preferably, the core-shell nanozyme C@Z@T has a particle size of 20-700 nm, a zeta potential of -26.9±0.721 mV, better dispersibility, and a more stable system.
[0008] Another aspect of the present invention further provides a method for preparing the core-shell nanozyme, comprising the steps of:
[0009] S1 Preparation of CeO2@ZIF-8 nanoparticles;
[0010] The spherical CeO2 nanoparticles and PVP are respectively dissolved in an organic solvent and mixed evenly, and then the product is immediately dispersed in a 2-methylimidazole / organic solvent solution after centrifugation until it is completely mixed; then, zinc salt is added, mixed and reacted to obtain the CeO2@ZIF-8 nanoparticles;
[0011] Preparation of S2 CeO2@ZIF-8@TA nanozyme;
[0012] The prepared CeO2@ZIF-8 nanoparticles are dispersed evenly in water, and then tannic acid TA is added to disperse evenly, and then centrifuged, washed, and dried to obtain the core-shell nanozyme.
[0013] Preferably, in step S1, CeO2 nanoparticles: PVP = 30-40 mg: 0.5-1.5 g.
[0014] Preferably, in step S2, CeO2@ZIF-8 nanoparticles: tannic acid = 0.1-0.5 g: 0.05-0.15 g.
[0015] Preferably, the reaction temperature in step S1 is 24-37°C, and the reaction temperature in step S2 is 25-35°C.
[0016] Preferably, the spherical CeO2 nanoparticles are prepared by hydrothermal synthesis.
[0017] Further preferably, the preparation method of the spherical CeO2 nanoparticles comprises the following steps: adding cerium nitrate salt to ethylene glycol, adding ultrapure water dropwise, fully dispersing at room temperature, then hydrothermally synthesizing at 180°C for 8-12h, centrifugally washing and drying at 110°C, and then calcining the dried product at 450-600°C, wherein Ce ion: ethylene glycol: ultrapure water = 4-5mmol:75-100mL:2-6mL.
[0018] In another aspect of the present invention, the use of the core-shell nanozyme in preparing wound dressings is provided, which is particularly suitable for diabetic wounds. Preferably, the concentration of the core-shell nanozyme in the wound dressing is 100-300 μg / mL, and more preferably, 200 μg / mL.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The CeO2 nanozyme of the present invention uses a metal organic framework material as a framework, and the core spherical CeO2 nano is placed therein, which can be gradually released as the metal organic framework decomposes, exerting its SOD and nanozyme activity to eliminate the excessive ROS generated by the wound surface. The outer side of the framework is also coated with tannic acid, which can improve the biocompatibility of the material and significantly improve the dispersibility of the nanozyme. The nanozyme of the present invention can spontaneously activate the generation and removal function of ROS, balance the steady state of ROS, and is suitable for wound healing, especially for diabetic wound healing. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 TEM image of C@Z@T of an embodiment of the present invention;
[0022] Figure 2 This is a particle size distribution diagram of C@Z@T in an embodiment of the present invention;
[0023] Figure 3 : is the Zeta potential of each nanoparticle in the embodiment of the present invention. DETAILED DESCRIPTION
[0024] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings and specific embodiments. Preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0025] In the description of the present invention, unless otherwise clearly defined, terms such as heating, cleaning, weighing, freezing, etc. should be understood in a broad sense, and technicians in the relevant technical field can reasonably determine the specific meanings of the above terms in the present invention in combination with the specific content of the technical solution.
[0026] In the description of the present invention, the description with reference to the terms "some embodiments", "examples", etc. means that the specific methods and materials described in conjunction with the embodiments or examples are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific methods and materials described can be combined in any one or more embodiments or examples in a suitable manner.
[0027] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0028] In the following examples and comparative examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.
[0029] Example 1
[0030] This embodiment provides a core-shell nanozyme, which is composed of a spherical CeO2 nanoparticle core, a zeolite imidazolate framework material ZIF-8 shell, and tannic acid TA coated on the shell. The specific preparation method thereof comprises the following steps:
[0031] (1) Preparation of CeO2@ZIF-8 nanoparticles
[0032] 35 mg of spherical CeO2 nanoparticles and 1 g of PVP were dissolved in 50 mL of methanol, respectively, and then mixed at 25 ° C for 24 h. The product was immediately redispersed in 50 ml of 25.6 mM 2-methylimidazole / methanol solution (methanol as solvent) after centrifugation, and stirred at 25 ° C for 20 min until completely mixed. Subsequently, Zn(NO3)2·6H2O (50 mL 25.2 mM, methanol solvent) was added and mixed for another 30 minutes until the product was completely reacted. The final product was centrifuged at 12,000 rpm, purified with methanol three times, and vacuum dried to obtain CeO2@ZIF-8 nanoparticles, recorded as C@Z.
[0033] (2) Preparation of CeO2@ZIF-8@TA nanoparticles
[0034] 0.3 g of the prepared CeO2@ZIF-8 was added to 100 mL of water and stirred for 30 min to make it uniformly dispersed. 0.1 g of tannic acid (TA) was added to the solution, stirred at 30 ° C for 10 min, centrifuged to obtain the precipitate, and washed with deionized water several times to remove the residual TA. Then, the wet CeO2@ZIF-8@TA nanoparticles were dried at 60 ° C for 12 h to obtain CeO2@ZIF-8@TA nanoparticles, recorded as C@Z@T.
[0035] The preparation method of the spherical CeO2 and ZIF-8 nanoparticles used in this embodiment is as follows:
[0036] (1) Preparation of spherical CeO2
[0037] Add 2g of cerium nitrate hexahydrate to 80mL of ethylene glycol, add 4mL of ultrapure water, and stir vigorously at room temperature for 30min. Transfer the mixed solution to a polytetrafluoroethylene liner, seal the stainless steel crystallization kettle with a lid, and perform hydrothermal synthesis at 180℃ for 8h. Centrifuge, wash repeatedly with ultrapure water, and then dry in an oven at 110℃ overnight. Grind the solid into powder, place it in a muffle furnace, heat it to 500℃ in air at a heating rate of 2℃ / min, and calcine it for 6h to obtain spherical CeO2 nanoparticles.
[0038] (2) Preparation of ZIF-8 nanoparticles
[0039] 3.3 g of 2-methylimidazole was dissolved in 70 mL of methanol solution to form solution A. Then 1.5 g of zinc nitrate hexahydrate was dissolved in 70 mL of methanol solution to form solution B. Solution A was slowly added to solution B to form a mixed solution, which was stirred at room temperature for 24 h and centrifuged. The obtained solid was washed three times with methanol solution and dried at 80°C overnight. The obtained sample was recorded as ZIF-8.
[0040] Figure 1This is the transmission electron microscopy image of the prepared C@Z@T nanoparticles. It can be seen that since the core cerium oxide is spherical, the obtained C@Z@T nanoparticles also present a uniform spherical shape and uniform size. Figure 2 Figure 2 is the particle size distribution of C@Z@T nanoparticles. It can be seen that the particle size is between 20-700nm and the average particle size is 214±8.246nm.
[0041] Figure 3 The Zeta potential statistics of each nanoparticle in the embodiment, including CeO2, ZIF-8, C@Z, C@Z@T, can be seen that the potentials of CeO2 and ZIF-8 nanoparticles are -7.56±1.58mV and 23.8±1.65mV respectively. The composite nanoparticles C@Z@T in the embodiment of the present invention are negatively charged as a whole due to the negative charge of tannic acid, and the Zeta potential is significantly improved after coating with tannic acid, and the size is -26.9±0.721mV, which indicates that the electrostatic repulsion between particles is increased, the stability is significantly improved, and the C@Z@T nanoparticles of the present invention have good dispersibility.
[0042] Comparative Example 1
[0043] A nanozyme, which is the spherical CeO2 nanoparticle in Example 1.
[0044] Comparative Example 2
[0045] A nanozyme, which is the ZIF-8 nanoparticle in Example 1.
[0046] Comparative Example 3
[0047] A nanozyme, which is the CeO2@ZIF-8 nanoparticle in Example 1.
[0048] Test example:
[0049] The nanozymes prepared in the examples and comparative examples were respectively prepared into solutions with a set concentration of 40-300 μg / mL using PBS (pH=7.4) for subsequent testing.
[0050] Table 1. Nanozyme concentration table of test examples
[0051] serial number Comparative Example 1 Comparative Example 2 Comparative Example 3 Example 1 Nanozyme Type <![CDATA[CeO2]]> ZIF-8 <![CDATA[CeO2@ZIF-8]]> C@Z@T Test Example 1 / / / 40 μg / mL Test Example 2 / / / 80 μg / mL Test Example 3 / / / 100 μg / mL Test Example 4 / / / 200 μg / mL Test Example 5 300 μg / mL Test Example 6 40 μg / mL / / / Test Example 7 300 μg / mL / / / Test Example 8 / 40 μg / mL / / Test Example 9 / 300 μg / mL / / Test Example 10 / / 40 μg / mL / Test Example 11 / / 300 μg / mL /
[0052] 1. Analysis of the in vitro antioxidant effect of nanozymes
[0053] Table 2 DPPH free radical scavenging rate (%)
[0054]
[0055] Test method: Prepare the sample according to the instructions of the commercially available DPPH free radical scavenging ability test kit, add the extract of the corresponding embodiment and comparative example to the DPPH solution, incubate in dark for 30 minutes, detect the absorbance at 515nm with a UV-visible spectrophotometer, and calculate the free radical scavenging rate.
[0056] The results show that: because the TA molecular structure has multiple phenolic hydroxyl groups (-OH), it has a strong hydrogen supply capacity, so it has outstanding performance in the antioxidant activity of scavenging free radicals. CeO2 has suitable oxidation vacancies and the ability to quickly convert Ce ions between tetravalent and trivalent ions. Therefore, in an acidic environment, CeO2 can exert the activity of peroxidase. Therefore, in the C@Z@T nanoparticles of the embodiment of the present invention, TA and CeO2 work together to show a good ability to scavenge free radicals.
[0057] 2. Analysis of antibacterial properties of nanozymes
[0058] Table 3 Antibacterial rate (%)
[0059]
[0060] Test method: Escherichia coli and Staphylococcus aureus were revived and cultured to the logarithmic growth phase, centrifuged, and the bacteria were collected and resuspended in physiological saline. The final bacterial solution concentration was 1×10 8 CFU / mL. Add 500 μL of nanozyme solution of corresponding concentration to a 24-well plate. Add 500 μL of saline to the control group. Then add 100 μL of diluted bacterial suspension and 500 μL of sterile saline to each well, incubate at 37°C for 24 hours, spread on LB agar plates after gradient dilution, and count.
[0061] The results show that CeO2 nanoparticles have a unique antibacterial mechanism due to their unique mixed valence state. The reversible conversion between the two states is a self-regenerating cycle that continues on the surface of the nanoparticles (Ce 4+ →Ce 3+ →Ce 4+ ). Therefore, CeO2 nanoparticles have a broad spectrum of antibacterial activity against bacteria and fungi. ZIF-8 in C@Z@T of the present invention can release Zn in a slightly acidic environment. 2+ and CeO2 drugs, exerting antibacterial effects. In addition, the outer layer coated TA is a natural polyphenol antibacterial small molecule with antioxidant, antibacterial, anti-inflammatory and biodegradable effects, which can be used in antibiotic-free antibacterial strategies. Its antibacterial activity can be exerted through various pathways, such as destroying the stability of cell membranes, penetrating cell membranes or inhibiting enzyme activity. Therefore, C@Z@T has excellent and unique antibacterial effects.
[0062] 3. Biocompatibility evaluation of nanozymes
[0063] Table 4 Cell survival rate (%)
[0064] Test Case 1 2 3 4 5 6 7 8 9 10 11 L929 cells% 99.99 99.15 99.06 98.59 97.56 99.52 97.55 99.58 97.1 99.88 98.71 293T cells% 99.56 98.45 98.16 95.17 94.59 99.35 96.68 99.55 97.31 99.25 94.38
[0065] Test method: Pre-sterilize the nanozyme by irradiating it with ultraviolet light for 24 hours. Then, prepare different concentrations of nanozyme solutions with culture medium for cell culture in subsequent experiments. L929 / 293T cells were digested with 0.25% trypsin, resuspended in DMEM, and seeded in a 48-well plate at a density of 10,000 cells per well. Cultured in a 37°C constant temperature carbon dioxide incubator (containing 5% CO2) for 24 hours until the cells adhered to the wall. Aspirate the culture medium, wash with PBS, add the corresponding concentration of nanozyme solution and continue to culture for 24 hours. After the culture is completed, aspirate the culture medium, wash with PBS 3 times, add 500 μL CCK-8 working solution (DMEM basal culture medium containing 10% CCK-8) to each well, incubate in a 37°C constant temperature carbon dioxide incubator (containing 5% CO2) for 30 minutes, and use a microplate reader to measure the absorbance (OD) at a wavelength of 450nm. Calculate the cell survival rate according to the formula: Cell survival rate (%) = (OD 实验组 -OD Blank ) / (OD 对照组 -OD Blank )×100%.
[0066] Result interpretation: The above results indicate that the core-shell nanozyme C@Z@T prepared in the embodiment of the present invention has acceptable cell biocompatibility.
[0067] In summary, it can be seen that the core-shell nanozyme C@Z@T of the present invention has good catalytic performance, good dispersibility, stable system, and the components cooperate with each other, significantly improving the antibacterial and antioxidant effects of CeO2 nanoparticles alone, and the components have good synergistic support. The core-shell nanozyme of the present invention can be used in wound dressings, especially for diabetic chronic wounds.
[0068] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0069] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A core-shell nanozyme, characterized in that: The invention consists of a spherical CeO2 nanoparticle core, a zeolite imidazole ester framework material ZIF-8 shell, and tannic acid TA coated on the shell.
2. The core-shell nanozyme according to claim 1, characterized in that The particle size of the core-shell nanozyme is 20-700 nm, and the zeta potential is -26.9±0.721 mV.
3. The method for preparing the core-shell nanozyme according to any one of claims 1 to 2, characterized in that: Includes steps: S1 Preparation of CeO2@ZIF-8 nanoparticles; The spherical CeO2 nanoparticles and PVP are respectively dissolved in an organic solvent and mixed evenly, and then the product is immediately dispersed in a 2-methylimidazole / organic solvent solution after centrifugation until it is completely mixed; then, zinc salt is added, mixed and reacted to obtain the CeO2@ZIF-8 nanoparticles; Preparation of S2 CeO2@ZIF-8@TA nanozyme; The prepared CeO2@ZIF-8 nanoparticles are dispersed evenly in water, and then tannic acid TA is added to disperse evenly, and then centrifuged, washed, and dried to obtain the core-shell nanozyme CeO2@ZIF-8@TA.
4. The preparation method according to claim 3, characterized in that: In the step S1, CeO2 nanoparticles: PVP = 30-40 mg: 0.5-1.5 g.
5. The preparation method according to claim 3, characterized in that: In the step S2, CeO2@ZIF-8 nanoparticles: tannic acid = 0.1-0.5 g: 0.05-0.15 g.
6. The preparation method according to claim 3, characterized in that: The reaction temperature in step S1 is 24-37°C, and the reaction temperature in step S2 is 25-35°C.
7. The preparation method according to claim 3, characterized in that: The spherical CeO2 nanoparticles are prepared by hydrothermal synthesis.
8. The preparation method according to claim 7, characterized in that: The preparation method of the spherical CeO2 nanoparticles comprises the following steps: adding cerium nitrate salt to ethylene glycol, dropping ultrapure water, fully dispersing at room temperature, then hydrothermally synthesizing at 180°C for 8-12h, centrifugally washing, drying at 110°C, and then calcining the dried product at 450-600°C, wherein Ce ion: ethylene glycol: ultrapure water = 4-5mmol: 75-100mL: 2-6mL.
9. Use of the core-shell nanozyme prepared according to any one of claims 1-2 or the preparation method according to any one of claims 3-8 in the preparation of wound dressings.
10. The use according to claim 9, characterized in that: The concentration of the core-shell nanozyme in the wound dressing is 100-300 μg / mL.
Citation Information
Patent Citations
Nano-enzyme with dual functions of resisting bacteria and removing excessive reactive oxygen species and preparation method of nano-enzyme
CN116019928A
Preparation method of tannic acid mediated cerium dioxide and copper sulfide composite nanomaterial
CN118387912A
Composite nano-enzyme for promoting wound healing and preparation method thereof
CN118717978A
Method for detecting and removing leucomalachite green and malachite green based on pH regulation MOF nano-enzyme function transformation strategy
CN118719147A
Cited By
A nanoparticle and a vesicle delivery system containing the nanoparticle, its preparation method and application
CN122664962A